Notice of Retraction: Relationship Between Refractive Index Change and Ti Concentration in Bulk Ti-Doped <tex Notation="TeX">$\hbox{LiNbO}_{3}$</tex> Crystal - De-Long Zhang; Fang Han; Ping-Rang Hua; Liang Sun; Dao-Yin Yu; Edwin Yue-Bun Pun (IEEE Photonics Journal, 2013)
Retracted.